2005
DOI: 10.1007/s00405-004-0883-0
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing function in patients with multiple-system atrophy with a clinical predominance of cerebellar symptoms (MSA-C)

Abstract: We investigated the swallowing function of 21 patients with multiple system atrophy with a clinical predominance of cerebellar symptoms (MSA-C) by videofluoroscopy (VF). Twenty-six VF examinations were performed at various time points, and they were divided into three groups according to the duration following disease onset: Group A had 1 to 3 years following disease onset (the early stage of the disease), group B had 4 to 6 years following disease onset (the middle stage of the disease), and group C had more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 11 publications
2
38
0
3
Order By: Relevance
“…One study demonstrated swallowing functions in patients with MSA-C [7]. They found that cerebellar dysfunction affects the swallowing function in the oral phase from an early stage of the disease, although it has little effect on the opening of the upper esophageal sphincter throughout all disease stages.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated swallowing functions in patients with MSA-C [7]. They found that cerebellar dysfunction affects the swallowing function in the oral phase from an early stage of the disease, although it has little effect on the opening of the upper esophageal sphincter throughout all disease stages.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete relaxation of the upper esophageal sphincter was seen in 23.1% of patients with MSA [15]. Higo et al have indicated that bolus transportation from the oral cavity to the pharynx is already disturbed in patients in the early stage of MSA-C [2]. The results of their study showed that 50% of the patients with MSA-C in the early stage (1−3 years following disease onset) and more than 85% in the late stage (>7 years following disease onset) suffered from delayed bolus transportation in the oral phase.…”
Section: Figurementioning
confidence: 99%
“…A study by Higo et al implied that the swallowing function in MSA patients may be more influenced by Parkinsonism than by cerebellar dysfunction and that Parkinsonism mainly affects the oral phase of swallowing [2]. They suggested that dysphagia in patients with MSA with predominant Parkinsonism (MSA-P) is caused by Parkinsonism, whereas in patients with MSA with predominant cerebellar ataxia (MSA-C), the progression of the cerebellar dysfunction and overlapping Parkinsonism worsens the tongue movements.…”
Section: Introductionmentioning
confidence: 99%
“…Waar verslikken door een parkinsonpatiënt uitblijft tijdens onderzoek met sliktests, omdat die kan compenseren door concentratie en het overwinnen van de hypokinesie, zal de MSA-patiënt door spierzwakte onvoldoende kunnen compenseren bij sliktests die uitdagen om sliksnelheid en volume te vergroten. 32 Krachtsverlies leidt ook tot moeite met kauwen en slikken van vaste voeding en ataxie verklaart bijvoorbeeld het zomaar verslikken in speeksel 33 . Terwijl sondevoeding bij parkinsonpatiënten ook in het gevorderde stadium van de ziekte maar bij 10% nodig zou zijn, 34 komt sondevoeding bij MSApatiënten in de klinische praktijk meer voor.…”
Section: Multisysteem Atrofieunclassified